Clinical Management of an Outbreak of Visceral Schistosomosis in Sheep in Rewa, Madhya Pradesh - Chaurasiya, Rupesh; Dixit, Alok Kumar; Dixit, Pooja (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Schistosomosis is an economically important disease of domestic animals and human being, mainly in the tropical  and subtropical zones of the world. Schistosomosis is now  recognized as the fifth major helminthosis of domestic animals  in the Indian sub-continent. The disease has been reported  in small ruminants by many workers (Cherian and D’Souza,  2009; Bhoyar et  al., 2012). The species which commonly  occur in India are Schistosoma nasale and S. spindale in  cattle, S. indicum in horses and sheep and S. incognitum in  pigs (D’Souza, 2006). S. indicum and S. spindale are the most  prevalent causative agents of visceral schistosomosis. The  disease is characterized by acute gastrointestinal symptoms  in small ruminants where diarrhoea is the main clinical sign.  Sometimes the disease is acute enough to cause death of the  animal due to fluid and electrolyte losses or due to emboli  formation by the parasite. The disease seems to be highly  prevalent, but is under-diagnosed and has not received due  attention.
Keywords: Clinical management; Outbreak; Sheep; Visceral Schistosomosis